Dziecko jako świadek totalitaryzmu. „Dzieci Syjonu“ a „Dzieci Gułagu“ - Lichtblau, Krzysztof (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article features a comparison of two very different collections of stories. What binds these narrations is the way they present the influence of totalitarian regimes on children’s lives. Children of Zion is a set of documents selected by Henryk Grynberg concerning the fate of Jewish children evacuated from the USSR to Palestine by general Władysław Anders. Children of the Gulag is a co-operative work by Cathy Frierson and Semyon S. Vilensky. They used source documents archived by the Memorial Association (Общество Мемориал) and Return (Возвращение), a historical-literary society which was established by Wileński himself. In the article the author aimed to present the main differences between the two totalitarian systems and how the systems caused dehumanization of childhood by means of exhausting labor, starvation, separation from parents and murder. What is more, the article contains a comparison of different attitudes towards the method of presenting historical facts and individual experiences. Hence, the scope of the work lies within discourse of representation / representation discourse.